Morphology and growth region analysis of carbon nanotubes growth in water-assisted flame synthesis - Mohd Fairus Mohd Yasin (Tanjung Malim, 2021)
Morphology and growth region analysis of carbon nanotubes growth in water-assisted flame synthesis by Mohd Fairus Mohd Yasin